Diet of albacore Thunnus alalunga from the waters of Mauritius (western Indian Ocean) inferred from stomach contents and fatty acid analysis. Issue 2 (2nd April 2020) - Dhurmeea, Z; Pethybridge, H; Romanov, EV; Appadoo, C; Bodin, N
Abstract : The diet of albacore Thunnus alalunga from their spawning ground in the waters of Mauritius was investigated. The stomach contents of 249 albacore individuals, caught by industrial longliners and artisanal fishers, was analysed, and the dominant prey taxa were selected for lipid and fatty acid (FA) analysis. The FA profiles of prey were compared with those of liver tissue of spawning-capable and post-spawning female albacore, using multivariate analysis. Whereas stomach content analysis identified cephalopods and crustaceans as the dominant prey items in number, FA-profile analysis identified crustaceans and fishes as the most-frequently consumed prey of post-spawning female albacore. In contrast, the FA profiles of spawning-capable albacore and those of prey showed very low similarity. Analysis of the prey suggests that although cephalopods, crustaceans and fishes could all provide albacore with the required lipids and FAs, cephalopod prey seem to be less desirable owing to their lower energy content (i.e. low in total lipid, triacylglycerol, 16:0, 18:0 and 18:1ω9). Instead, the most beneficial food appeared to be locally available fishes, which are more energy-rich and have a higher docosahexaenoic acid/ eicosapentaenoic acid ratio. These results provide new information on the trophic ecology of albacore, promote our understanding of the importance of prey type for successful reproduction of albacore, and highlight the advantages of FA profiling to study diet.